Water Transfer Between Bamboo Culms in the Period of Sprouting - Fang, Dongming; Mei, Tingting; Röll, Alexander; Hölscher, Dirk (Frontiers in Plant Science, 2019)
Bamboo culms are connected to neighboring culms via rhizomes, which enable resource exchange between culms. We assessed water transfer between established and neighboring, freshly sprouted culms by thermal dissipation probes inserted into culms and the connecting rhizome. During the early phase of sprouting, highest sap flux densities in freshly sprouted culms were observed at night, whereas neighboring established culms had high sap flux densities during daytime. After leaf flushing on freshly sprouted culms, the nighttime peaks disappeared and culms switched to the diurnal sap flux patterns with daytime maxima as observed in established culms. Thermal dissipation probes in rhizomes indicated water flowing from the established to the freshly sprouted culms. When the established culms of a clump were cut, freshly sprouted culms without leaves reduced sap flux densities rates by 79%. Our findings thus suggest that bamboos exchange water via rhizomes and that nighttime fluxes are highly important for the support of freshly sprouted culms. The (water) resource support may facilitate the very fast growth of the bamboo shoots, and enable the colonizing of new places.